Avaliação do estado micronutricional e de estresse oxidativo em idosos - Paniz, Clóvis (2007)
The increase in life expectancy has made the aging of the population a global phenomenon. Projections point to a growth of greater than 300% in the number of elderly people over the next 50 years. The rapid growth of the elderly population, mainly in developing countries has become a public health problem. In this age group, non transmissible chronic diseases are very common, mainly those of a nutritional origin. Although aging is a complex phenomenon, oxidative stress seems to play an important role in this process. On the other hand, there are few studies evaluating the levels of antioxidants in the diet and oxidative stress biomarkers in healthy elderly. These data could be useful to understand the role of oxidative stress in physiopathological changes associated with human aging, both in institutionalized elderly and in non-institutionalized elderly. In the this study, an analysis was made of oxidative stress biomarkers such as reduced glutathione (GSH), malondialdehyde (MDA), protein carbonyls (PCO) and δ-aminolevulinate dehydratase (ALA-D) as well as, some antioxidants from the diet such as vitamin C, E, B12 and folate; of in institutionalized elderly women (n= 45; 71 ± 6 years old) from a public retirement home and non-institutionalized elderly women (n= 22; 68 ± 6 years old). Moreover, the nutritional status was evaluated through a determination of serum albumin, hemoglobin and the body mass index (BMI) as well as a lipidic profile. The mental state was assessed through the Mini Mental State Examination (MEEM). In the institutionalized group, vitamin C levels were significantly decreased and vitamin E levels were significantly increased. The levels of folate and vitamin B12 did not show significant differences between the groups and a low deficiency incidence was found for both vitamins. However, both vitamins were within the normal range established for adults. GSH and PCO did not present significant differences between the groups, while MDA and ALA-D were significantly increased in the non-institutionalized group. The institutionalized group had a lower cognitive performance, showing scores significantly decreased. Moreover, positive correlations were found between vitamin C and ALA-D, vitamin C and albumin, vitamin C and hemoglobin, vitamin C and the mental state and between folate and MEEM. Moreover, a negative correlation was found between vitamin E and both PCO and MDA, between PCO and ALA-D and between ALA-D and age. Thus, through the results found in the institutionalized elderly women, it can be suggested that the evaluated micronutrient levels, considered normal for adults, could be insufficient for the elderly. Vitamin C may protect some blood proteins from oxidative effects, especially those with thiol groups. Vitamin E levels may have an effect on MDA levels, protecting the lipid membrane from lipoperoxidation, and also, the carbonylation of proteins. In addition, both vitamin C and folate demonstrated protection against cognitive impairment in elderly women. The ALA-D was presented as a possible oxidative stress biomarker to evaluate oxidative stress in elderly.